A COMPARATIVE STUDY OF THE IMPLEMENTATION OF PANCASILA VALUES AMONG MILLENIALS AND GENERATION Z IN THE ERA OF MODERNIZATION - Handayani, Nur Fitri; Wingkolatin, Wingkolatin; Fajriatin, Kwartanti (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2025)
Millenials and Generation Z show significant differences in their understanding and application of Pancasila values, influenced by different social and cultural background. Millenials were born between the early 1980 and mid-1990s, have better access to technology and stable life experiences, so they are better able to internalize Pancasila values in their daily lives. In contrast, Gen Z, who were fully raised in the digital era, tend to be more individualistic and influenced by global culture, so Pancasila values are often considered less relevant. This article aims to analyze the differences in the implementation of Pancasila values between the two generations, identify the challenges faced and explore innovation in education to improve Gen z understanding of Pancasila, with a technology based approach that suits Gen z preferences, it is hoped that Pancasila values will remain relevant and applicable amidst modernization. Keywords: Millennial Generation, Gen Z, Pancasila, Education, Globalization.